Методичні особливості техніко-економічного аналізу перспектив розвитку локальної генерації на базі мікро-ТЕЦ як складової електроенергетичного комплексу - Grigoriev R.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
The methodical features of economical viability estimation for the micro CHP large scope usage in the private sector of energy consumption where considered.